Black Girl Refusals and Reimaginings: Theorizing Liberatory Black Girlhoods Across the Diaspora: The Black Girlhood Studies Collection. Issue 2 (1st June 2021) - Unknown
Abstract : Aria S. Halliday (ed.). 2019. The Black Girlhood Studies Collection . Toronto: Women's Press.